Gradient estimates for p-Laplacian equation in composite Reifenberg domains. (March 2016) - Zhang, Chao
Abstract: We obtain a local gradient estimate for weak solutions of p -Laplacian type equation in a non-smooth domain composed of a finite number of disjoint subdomains with ( δ 0, R ) -Reifenberg flat boundaries. This kind of domain was called ( δ 0, R ) composite-Reifenberg domain, which allows certain subdomain to exist with highly non-smooth boundaries worse than Reifenberg domain. Our results improve the known results for such equations.